Spectrophotometric determination of sotalol in tablets - Y. M. Zhuk; S. O. Vasyuk (Фармацевтичний журнал, 2018)
In this investigation a visible spectrophotometric method for the determination of sotalol based on the absorbance of colored product of the reaction between sotalol hydrochloride and bromcresol purple in acetone medium at 399 nm measurement was developed. The optimal conditions for the quantitative determination of sotalol hydrochloride in the content of pharmaceutical drugs were established. The stoichiometric relationship coefficients between sotalol hydrochloride and bromcresol purple were determined. The validation of the worked out procedure on such validated characteristics as linearity, precision, accuracy and robustness was carried out.